HOW INDONESIAN NOVICE EFL TEACHERS BUILD AGENCY: INSIGHTS FROM A CASE STUDY - Fini Feronisa; Ngadiso Ngadiso; Endang Setyaningsih (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Teacher agency has become an essential focus in understanding how teachers navigate instructional demands and professional challenges. This study investigates the agency of Indonesian novice English as a Foreign Language (EFL) teachers by examining four core properties of human agency as proposed by Bandura: intentionality, forethought, self-reactiveness, and self-reflectiveness. Employing a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and scenario-based vignettes involving three novice English teachers in Banyumas. The data were analyzed using Miles, Huberman, and Saldana’s (2014) interactive model, which involved data condensation, display, and conclusion drawing. These findings demonstrate that Indonesian novice EFL teachers exhibit all four core agency properties, intentionality, forethought, self-reactiveness, and self-reflectiveness, which are reflected in their classroom practices in varying degrees. While all participants expressed strong intentionality, their enactments of the other properties were predominantly reactive, shaped by immediate classroom challenges such as limited resources and low students’ motivation. The findings contribute to developing contextually informed teacher education by highlighting the complex interaction between personal goals and external demands in shaping agency. The study highlights the need for structured support and professional mentoring to help novice teachers strengthen their agency and transition toward more proactive and sustainable teaching practices.